Online Workshop with Service Learning Method to Meet the Needs of Tinkercad Users from the Engineering Field - Winda Halim; Erwani Merry Sartika; Novie Theresia Br. Pasaribu; Audyati Gany; Rainisa Maini Heryanto; Markus Tanubrata (Faculty of Smart Technology and Engineering, Universitas Kristen Maranatha, Bandung, Indonesia, 2023)
The COVID-19 pandemic has greatly affected the learning process in practice, especially for people in the engineering field. Activities stopped and learning activities become very obstructed for a long time. Tinkercad is a simulator application that could be used as a learning tool or medium in engineering. The service learning method is used as a way of teaching and learning that links positive and meaningful action in society. Service learning uses demonstrations and experiments are used to transfer knowledge to society. A workshop elaborating the use of Tinkercad based on the service learning method was carried out online through community service activities to meet community needs in the engineering field. The workshop results showed that the service learning method was sufficient to help the community to meet the learning needs of engineering practices. A thorough demonstrations by instructors and experiments done by participants guided by assistants, produced a satisfactory result for more than 90% of the workshop participants. Periodic literacy provision was a follow-up to improve the abilities of all participants who have take part in workshop activities.